2008
DOI: 10.1007/s00213-008-1081-3
|View full text |Cite
|
Sign up to set email alerts
|

The postweaning social isolation in C57BL/6 mice: preferential vulnerability in the male sex

Abstract: We conclude that social isolation in mice represents a valuable tool for the examination of candidate genes within the context of the "two-hit" hypothesis of the aetiological processes in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
52
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 123 publications
(198 reference statements)
13
52
3
Order By: Relevance
“…A consistent pattern of results was replicated in experiment 2 (Table 1). Indeed, the lack of startle habituation in C57BL/6 mice is a robust result in agreement with earlier reports (Pietropaolo et al 2008;Yee et al 2004aYee et al , 2005. Given that impairment in startle reflex habituation is also present in schizophrenia patients and may be related to impaired selective attention (Geyer and Braff 1987;Geyer et al 1990), should one also consider this strain-specific trait as a potential schizophrenia-related endophenotype?…”
Section: Discussionsupporting
confidence: 75%
“…A consistent pattern of results was replicated in experiment 2 (Table 1). Indeed, the lack of startle habituation in C57BL/6 mice is a robust result in agreement with earlier reports (Pietropaolo et al 2008;Yee et al 2004aYee et al , 2005. Given that impairment in startle reflex habituation is also present in schizophrenia patients and may be related to impaired selective attention (Geyer and Braff 1987;Geyer et al 1990), should one also consider this strain-specific trait as a potential schizophrenia-related endophenotype?…”
Section: Discussionsupporting
confidence: 75%
“…The mean startle reaction (ln-transformed) on the two blocks was as follows: first block: high-PPI = 4.23, low-PPI = 4.29, SE = .14; last block: high-PPI = 4.20, low-PPI = 4.47, SE = .15. The lack of clear startle habituation here was expected as we have repeatedly shown that C57BL/6 mice did not show reliable stable habituation (e.g., Pietropaolo, Singer, Feldon, & Yee, 2008;Singer, Feldon, & Yee, 2009b;Singer & Yee, 2012;Yee et al, 2004aYee et al, , 2005 in our laboratory. Singer et al (2013) reported that while some subjects (C57BL/6 mice) showed habituation, a similar number showed sensitization.…”
Section: Resultssupporting
confidence: 49%
“…In a study of another AD model, and using physical exercise as intervention, Pietropaolo et al (2008) found the result to be influenced by gender. Stress per se, on the other hand, is a strong negative regulator of adult neurogenesis (Gould et al, 1997), whereas gender differences appear to be minimal.…”
Section: Discussionmentioning
confidence: 94%